Dysregulation of protein succinylation and disease development - Hou, Xiaoli; Zhu, Lijuan; Xu, Haiying; Shi, Jie; Ji, Shaoping (Frontiers in Molecular Biosciences, 2024)
As a novel post-translational modification of proteins, succinylation is widely present in both prokaryotes and eukaryotes. By regulating protein translocation and activity, particularly involved in regulation of gene expression, succinylation actively participates in diverse biological processes such as cell proliferation, differentiation and metabolism. Dysregulation of succinylation is closely related to many diseases. Consequently, it has increasingly attracted attention from basic and clinical researchers. For a thorough understanding of succinylation dysregulation and its implications for disease development, such as inflammation, tumors, cardiovascular and neurological diseases, this paper provides a comprehensive review of the research progress on abnormal succinylation. This understanding of association of dysregulation of succinylation with pathological processes will provide valuable directions for disease prevention/treatment strategies as well as drug development.